Migratory Behavior of an Eastern North Pacific Gray Whale From Baja California Sur to Chirikov Basin, Alaska - Urbán R, Jorge; Jiménez-López, Esther; Guzmán, Héctor M.; Viloria-Gómora, Lorena (Frontiers in Marine Science, 2021)
Eastern gray whales undertake annual migrations between summer feeding grounds in the Bering and Chukchi Seas and winter breeding and calving lagoons in the west coast of Baja California, Mexico. On February 12, 2017, three adult gray whales were sighted at San José del Cabo, Mexico, in which one individual, named “María,” was tagged using a satellite telemetry transmitter (PTT). The PTT stopped the signal on July 11, 2017. María traveled 11,387 km during 149 days from San José del Cabo to the Chirikov Basin. The migration route was aligned close to the coastline (<23 km) from February to April. After passing Kodiak Island in May, María started traveling far away from the coastline (>70 km) into the Bering Sea, including the Chirikov Basin. During March, April, and May, María traveled long distances at relatively high speeds, in contrast to the lower speed during February, early March, and the arrival time to the feeding areas in May, June, and July. The total distance traveled by María during its migration from Ojo de Liebre Lagoon to the Chirikov Basin was 8,863 km during 61.5 days with an average speed of 5.5 km h–1; this excludes the 14 days and 591 km that María spent feeding on the coast of Kodiak Island in late April. The information provided by this tagged whale documents a single whales’ migration, which is consistent with previous studies and constitutes the most complete northbound reported migration of an eastern gray whale.